2013
DOI: 10.1080/14772019.2013.764935
|View full text |Cite
|
Sign up to set email alerts
|

Postcranial axial skeleton ofEuropasaurus holgeri(Dinosauria, Sauropoda) from the Upper Jurassic of Germany: implications for sauropod ontogeny and phylogenetic relationships of basal Macronaria

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis. The accuracy of the Content s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
234
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(256 citation statements)
references
References 81 publications
12
234
5
5
Order By: Relevance
“…documented cranial changes between immature and mature specimens of Diplodocus (or Diplodocinae indeterminate [Tschopp et al, 2015]), which include the development of proportionally larger orbits, rounded and narrower premaxilla, and a more anteriorly situated tooth row. Wedel (2003Wedel ( , 2005Wedel ( , 2009, Schwarz et al (2007a), and Carballido and Sander (2014) have demonstrated that the complexity of pneumatic architecture has increased through sauropodomorph phylogeny and likewise increased through ontogeny. Salgado (1999) suggested a link between the degree of neural spine bifurcation and ontogeny in diplodocids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…documented cranial changes between immature and mature specimens of Diplodocus (or Diplodocinae indeterminate [Tschopp et al, 2015]), which include the development of proportionally larger orbits, rounded and narrower premaxilla, and a more anteriorly situated tooth row. Wedel (2003Wedel ( , 2005Wedel ( , 2009, Schwarz et al (2007a), and Carballido and Sander (2014) have demonstrated that the complexity of pneumatic architecture has increased through sauropodomorph phylogeny and likewise increased through ontogeny. Salgado (1999) suggested a link between the degree of neural spine bifurcation and ontogeny in diplodocids.…”
Section: Introductionmentioning
confidence: 99%
“…Woodruff and Fowler (2012) showed that small (presumably immature) diplodocids exhibited rounded to weakly bifurcated neural spines, whereas neural spines were fully bifurcated in larger (and presumably more mature) individuals. Based on this observation, it was suggested that the degree of bifurcation could be used to infer maturity in diplodocids (and other methodologies have used morphology to predict maturity; such as the Morphologic Ontogenetic Stage [MOS] of Carballido and Sander, 2014; or the ontogenetic trajectory stages of Ikejiri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, nueva información proveniente de la anatomía dentaria ubica a Amygdalodon por fuera de Eusauropoda (Carballido y Pol, 2010;Carballido y Sander, 2013).…”
Section: Reseña De Los Principales Grupos De Sauropodomorpha Sauropodunclassified
“…Hasta la fecha, la filogenia de jerarquías altas de los saurópodos está relativamente bien establecida, compuesta por Sauropoda basales (e.g., Lessemsaurus Bonaparte, 1999, del (Carballido y Sander, 2013) (Fig. 1.2).…”
unclassified
See 1 more Smart Citation